Histopathological changes and clinical responses of Buruli ulcer plaque lesions during chemotherapy: a role for surgical removal of necrotic tissue? - Marie-Thérèse Ruf; Ghislain Emmanuel Sopoh; Luc Valère Brun; Ange Dodji Dossou; Yves Thierry Barogui; Roch Christian Johnson; Gerd Pluschke (Public Library of Science (PLoS), 2011)
BACKGROUND: Buruli ulcer (BU) caused by Mycobacterium ulcerans is a necrotizing skin disease usually starting with a subcutaneous nodule or plaque, which may ulcerate and progress, if untreated, over months and years. During the currently recommended antibiotic treatment with rifampicin/streptomycin plaque lesions tend to ulcerate, often associated with retarded wound healing and prolonged hospital stays. METHODOLOGY/PRINCIPAL FINDINGS: Included in this study were twelve laboratory reconfirmed, HIV negative BU patients presenting with plaque lesions at the CDTUB in Allada, Benin. Punch biopsies for histopathological and immunohistochemical analysis were taken before start of treatment and after four to five weeks of treatment. Where excision or wound debridement was clinically indicated, the removed tissue was also analyzed. Based on clinical judgment, nine of the twelve patients enrolled in this study received limited surgical excision seven to 39 days after completion of chemotherapy, followed by skin grafting. Lesions of three patients healed without further intervention. Before treatment, plaque lesions were characterized by a destroyed subcutis with extensive necrosis without major signs of infiltration. After completion of antibiotic treatment partial infiltration of the affected tissue was observed, but large necrotic areas remained unchanged. CONCLUSION/SIGNIFICANCE: Our histopathological analyses show that ulceration of plaque lesions during antibiotic treatment do not represent a failure to respond to antimycobacterial treatment. Based on our results we suggest formal testing in a controlled clinical trial setting whether limited surgical excision of necrotic tissue favours wound healing and can reduce the duration of hospital stays.